Synthesis and characterization of nanoparticle incorporated polymer composite materials - Md. Najmul, Kabir Chowdhury (2014)
his thesis is composed with the aim of the synthesis of nanoparticle impregnated oil palm fibre reinforced composites. This aim is initiatedwith the synthesis of copper nanoparticles (CuNPs) at ambient condition in aqueous medium using copper chloride precursor,sodium borohydride (SBH), ascorbic acid and polyvinyl alcohol (PVA) of two different molecular weights (Mws). The formationand characterization of the nano copper sols are studied. The physical appearance of prepared sol has been found to be stable for a couple of weeks when kept in ambient atmospheric condition, as confirmed by ultraviolet-visible absorption spectroscopy. Transmission electron microscopy exhibits spherical morphology of CuNPs with an average size of 3.5±1.1 nm.The effect of SBH amount and PVA (wt.% and Mws) on the size of CuNPs are also delineated. As a potential application of CuNPs, theywere impregnatedon/into oil palm empty fruit bunch (EFB) fibres via cationization process. Conventionally, same EFBfibres were also treated with alkali solutions. Treated fibres were characterized by Fourier transformed infrared (FTIR) spectroscopy, X-ray diffraction (XRD) study, field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) study and thermogravimetric analysis (TGA). Numerous physical and mechanical properties of different single fibres were measured and especially the mechanical properties were analyzed by the Griffith model and Weibull statistical distribution. The weak link scaling of Weibull analysis has provided valuable information to scale the strength of one EFB fibre to predict the strength of other one. A significant increase in mechanical property of CuNPs modified fibres with respect to the control ones has been observed. CuNPs impregnated EFB fibres show increases of tensile strength (~34%) and antifungal activity (24%) with respect to control fibres.These findings strongly suggest that CuNPs can be used as an effective agent in natural fibres to improve their mechanical property and durability. Therefore, different doses CuNPs impregnated strong and durable fibres were used to develop theCuNPs impregnated fibre reinforced unsaturated polyester resin nanocomposite. The composite behaviour, mechanical property and biodegradability have been investigated systematically by using the commonly used techniques such as FTIR, XRD, FESEM, TGA, differential scanning calorimetry (DSC), universal tensile testing tester, etc. The developed nanocomposites mechanical properties and biodegradability were optimized by response surface methodology (RSM) also. The biodegradability of the developed composites was inversely proportional to the CuNPs loadings. The change of weight gain (due to moisture absorption) for all samples is highly related with a typical Fickian diffusion behaviour. Moreover, higher mechanical (tensile and flexural) performances were obtained for CuNPs treated fibre (NF) composites compared to those of untreated fibre based composites. Among all of the fibre reinforced composites tested, NF reinforced unsaturated polyester resin composites (30% fibre) registered for the highest mechanical properties. It was found that standard micromechanical models (Rule of Mixture, Inverse Rule of Mixture and Halpin-Tsai Model) which are commonly used to predict the strength of traditional synthetic fibre composites can be applied to such natural fibre systems with mixed success. Throughout the work, three schemes were proposed.The obtained properties of the developed nanocomposites indicate that they can be considered for both indoor-outdoorapplications